Experiences in personality : research, assessment, and change - Merrens, Matthew R.; Brannigan, Gary G. (New York : John Wiley & Sons, 1998)
This book is about: Studying personality; Classical psychoanalytical perspective; Behavioral perspectives; ...
Keywords: Personality; Personality